2013
DOI: 10.1016/j.yjmcc.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of mRNA identifies re-expression of fetal splice variants in cardiac hypertrophy

Abstract: Cardiac hypertrophy has been well-characterized at the level of transcription. During cardiac hypertrophy, genes normally expressed primarily during fetal heart development are reexpressed, and this fetal gene program is believed to be a critical component of the hypertrophic process. Recently, alternative splicing of mRNA transcripts has been shown to be temporally regulated during heart development, leading us to consider whether fetal patterns of splicing also reappear during hypertrophy. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
(75 reference statements)
1
28
0
Order By: Relevance
“…Intriguingly, much like reactivation of selected fetal genes, some fetal splice isoforms are also re-expressed in the stressed or diseased heart. 70 For example, splicing of the sarcomeric proteins titin and myomesin is regulated during development, and their fetal isoforms are re-expressed in the stressed heart. 71 Apart from the re-expression of fetal isoforms, it is known that alternative splicing is broadly altered in cardiac hypertrophy and disease.…”
Section: Alternative Splicing In Diseasementioning
confidence: 99%
“…Intriguingly, much like reactivation of selected fetal genes, some fetal splice isoforms are also re-expressed in the stressed or diseased heart. 70 For example, splicing of the sarcomeric proteins titin and myomesin is regulated during development, and their fetal isoforms are re-expressed in the stressed heart. 71 Apart from the re-expression of fetal isoforms, it is known that alternative splicing is broadly altered in cardiac hypertrophy and disease.…”
Section: Alternative Splicing In Diseasementioning
confidence: 99%
“…Global alternative splicing profiling has been done in the diseased heart, including cardiac hypertrophy and heart failure. 34,35 For example, an earlier study compared pressure overload-induced cardiac hypertrophy and heart failure in the mouse heart using deep RNA-sequencing and revealed a global change of alternative splicing in the failing murine heart. 35 More recently, Ames et al and other groups also identified a significant number of alternative splicing events during cardiac hypertrophy in rats.…”
Section: Alternative Rna Splicing In Transcriptome Regulationmentioning
confidence: 99%
“…35 More recently, Ames et al and other groups also identified a significant number of alternative splicing events during cardiac hypertrophy in rats. 34,36 For splicing regulators, it is suggested that the expression of PTB and ASF/SF2 is altered in the pressure overload-induced hypertrophic heart. 37 The transcriptome signature and RNA splicing events have also been profiled in human heart disease.…”
Section: Alternative Rna Splicing In Transcriptome Regulationmentioning
confidence: 99%
“…While physiological hypertrophy leads to an improvement in life quality by increasing oxygenation capacity and maximal cardiac output, pathological hypertrophy leads to a progressive deterioration of cardiac function ending with fatal heart failure (Song et al 2012 ). RNA-seq was also recently applied to show that the developmental AS program is recapitulated during pressure-overload cardiac hypertrophy in rats ( Ames et al 2013 ). The comparison of AS events in hypertrophy and during heart development revealed a signifi cant overlap, suggesting that hypertrophic hearts reuse some of the regulatory mechanisms involved in normal development (Ames et al 2013 ).…”
mentioning
confidence: 99%
“…RNA-seq was also recently applied to show that the developmental AS program is recapitulated during pressure-overload cardiac hypertrophy in rats ( Ames et al 2013 ). The comparison of AS events in hypertrophy and during heart development revealed a signifi cant overlap, suggesting that hypertrophic hearts reuse some of the regulatory mechanisms involved in normal development (Ames et al 2013 ).…”
mentioning
confidence: 99%